Durability Assessment Of Oyster Shell-Embedded Concrete Subjected To Freeze-Thaw Cycle In ASTM C666 (International Journal of Environmental Sciences, 2025)
This study investigates at the mechanical characteristics of concrete that uses oyster shell as a coarse aggregate, focussing particular attention to how well it performs in ASTM C666-recommended freeze-thaw cycles. In order to assess any potential benefits or drawbacks of using oyster shells in concrete mixes, the research looked at their chemical makeup and compatibility with cement paste. The mechanical features of both fresh and cured concrete were examined at different oyster shell replacement amounts, from 0% to 50%. The outcomes showed that the workability of the concrete declined as the replacement rate increased, despite the fact that there was no discernible chemical interaction between the oyster shell and the cement paste. Compared to traditional aggregates, oyster shells have a lower specific gravity and a larger porosity, which is probably the cause of this decrease in workability. Likewise after exposure to freeze-thaw cycles, a significant 20% decrease in compressive strength was seen at a 30% replacement level, illustrating the need of optimising the percentage of oyster shells to achieve a balance between sustainability and structural performance. According to these results, oyster shells may be a viable substitute aggregate, but their proportions must be monitored closely in order to assure the appropriate mechanical performance and longevity of concrete, specifically in cold climates.